Mapping Indonesia's Maritime Defense Strategy: A Critical Analysis of Enforcement Effectiveness Against Territorial Violations in the North Natuna Sea - Suseto, Buddy; Pandjaitan, Manahan Budiarto; Nugroho, Mohammad Ali; Cahyono, Ugik (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
This study examines Indonesia’s maritime defense strategy in the North Natuna Sea, focusing on the identification of major threats and the assessment of enforcement effectiveness. A descriptive qualitative method was employed, utilizing interviews, observations, and document analysis, with data analyzed through Miles and Huberman’s model. The findings show that Indonesia applies a layered maritime defense that integrates military power, diplomacy, law enforcement, and community participation. Key threats consist of illegal, unreported, and unregulated (IUU) fishing, grey zone tactics, unauthorized seabed surveys, and transnational smuggling. Joint operations involving the Navy, the Maritime Security Agency (Bakamla), and the Ministry of Marine Affairs and Fisheries were found to reduce violations, with an estimated Rp774.3 billion in potential state losses prevented between January and May 2025. However, the overall effectiveness remains limited due to constrained naval assets, weak interagency coordination, and regional geopolitical pressures. The study underscores the significance of a multi-actor enforcement approach and recommends the establishment of integrated command centers, modernization of AI-based surveillance systems, and the strengthening of defense diplomacy to reinforce Indonesia’s maritime security posture.